Molecular and functional analysis of the novel cfr(D) linezolid resistance gene identified in Enterococcus faecium. (11th April 2020) - Guerin, François; Sassi, Mohamed; Dejoies, Loren; Zouari, Asma; Schutz, Sacha; Potrel, Sophie; Auzou, Michel; Collet, Anaïs; Lecointe, Didier; Auger, Gabriel; Cattoir, Vincent
Abstract: Objectives: To characterize the novel cfr (D) gene identified in an Enterococcus faecium clinical isolate (15-307.1) collected from France. Methods: The genome of 15-307.1 was entirely sequenced using a hybrid approach combining short-read (MiSeq, Illumina) and long-read (GridION, Oxford Nanopore Technologies) technologies in order to analyse in detail the genetic support and environment of cfr (D). Transfer of linezolid resistance from 15-307.1 to E. faecium BM4107 was attempted by filter-mating experiments. The recombinant plasmid pAT29Ω cfr (D), containing cfr (D) and its own promoter, was transferred to E. faecium HM1070, Enterococcus faecalis JH2-2 and Escherichia coli AG100A. Results: As previously reported, 15-307.1 belonged to ST17 and was phenotypically resistant to linezolid (MIC, 16 mg/L), vancomycin and teicoplanin. A hybrid sequencing approach confirmed the presence of several resistance genes including vanA, optrA and cfr (D). Located on a 103 kb plasmid, cfr (D) encoded a 357 amino acid protein, which shared 64%, 64%, 48% and 51% amino acid identity with Cfr, Cfr(B), Cfr(C) and Cfr(E), respectively. Both optrA and cfr (D) were successfully co-transferred to E. faecium BM4107. When expressed in E. faecium HM1070 and E. faecalis JH2-2, pAT29Ω cfr (D) did not confer any resistance, whereas it was responsible for an expected PhLOPSA resistance phenotype in E. coli AG100A. Analysis of the genetic environment of cfr (D) showed multiple IS 1216 elements, putatively involved in its mobilization. Conclusions: Cfr(D) is a novel member of the family of 23S rRNA methyltransferases. While only conferring a PhLOPSA resistance phenotype when expressed in E. coli, enterococci could constitute an unknown reservoir of cfr (D).